(untitled) (Applied Biological Research, 2011)
The present study demonstrates the effect of nano-ZnO particles on growth of mung bean (Vigna radiata) and chickpea (Cicer arietinum) seedlings. The study was conducted in plant agar media to prevent precipitation of water insoluble nanoparticles in test units. Various concentrations of nano-ZnO particles in suspension form were introduced to the agar media and its effect on root and shoot growth of seedlings examined. Analytical techniques like optical microscopy and scanning electron microscopy were used to study the architecture of root. Inductive coupled plasma (ICP) was used to determine the uptake of nano-ZnO particles by root. The best response of nano-ZnO on mung bean was observed at 20 ppm and on chickpea at 1 ppm, beyond these concentrations the seedling showed retardation in growth and de